Do Renewable Energy Policies Reduce Carbon Emissions? On Caps and Intra-Jurisdictional Leakage - Grischa Perino; Johannes Jarke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Climate policies overlapping a cap-and-trade scheme are generally considered not to change domestic emissions. In a two-sector general equilibrium model where only one sector is covered by a cap, we find that such policies do have a net impact on carbon emissions through inter-sectoral leakage. Promotion of renewable energy reduces emissions if tax-funded, but can increase emissions if funded by a levy on electricity. Replacing fossil fuels by electricity in uncapped sectors (e.g. power-to-heat or electric cars) and increases in the efficiency of electricity use reduce domestic emissions. Moreover, the commonly used measure to assess renewable energy policies is biased.
Keywords: Q58; Q48; H23; 330